Mechanistic applications of click chemistry for pharmaceutical drug discovery and drug delivery. Issue 11 (November 2017) - Meghani, Nilesh M.; Amin, Hardik H.; Lee, Beom-Jin
Graphical abstract: Highlights: Basic mechanism for all the discussed click reaction has been shown. Many new enzyme inhibitors was identified by drug discovery using click approaches. Drug delivery by bioconjugation was significantly impacted by advent of click chemistry. Abstract : The concept of click chemistry (CC), first introduced by K.B. Sharpless, has been widely adopted for use in drug discovery, novel drug delivery systems (DDS), polymer chemistry, and material sciences. In this review, we outline novel aspects of CC related to drug discovery and drug delivery, with a brief overview of molecular mechanisms underlying each click reaction commonly used by researchers, and the main patents that paved the way for further diverse medicinal applications. We also describe recent progress in drug discovery and polymeric and carbon material-based drug delivery for potential pharmaceutical applications and advancements based on the CC approach, and discuss some intrinsic limitations of this popular conjugation reaction. The use of CC is likely to significantly advance drug discovery and bioconjugation development. Teaser: Click chemistry is set to develop new potential molecules and biomaterials for treatment of various diseases, drug delivery and diagnostics, respectively.